Empowering Small Entrepreneurs: The Role of English in Attracting International Tourists - Subekti, Priyo; Lukman, Syauqy; Nugraha, Aat Ruchiat (Journal of English Language and Education, 2025)
The research investigates the importance of English skills in improving the performance of small-scale business practitioners in the tourism industry on Pangandaran Beach. This area is unique and environmentally friendly and serves both domestic and international tourists which in turn provide vast opportunities for supply. However, entrepreneurs are unable to articulate some ideas and interact better with foreign tourists because of the language barrier which limits their ability to market local culture, services and make money.  Data collected includes quantitative data from 46 respondents and qualitative interviews. From these it can be discerned that English skills vary, with the majority of entrepreneurs appearing to be educated however with limited command of the language. Some of the challenges were time going to classes, finances, and language barriers. Notably however, contact with visitors, especially foreign nationals, is deemed abundant and English is deemed important to use in order to achieve satisfaction. The results illustrate the possibility that better English proficiency can lead to better quality of interaction, more positive feedback, and increased earnings. The study centers around flexible and inexpensive English training that is supplemented with the needs of the entrepreneurs like online, role gaming and etc. These kinds of activities are crucial in enabling small scale businesses to compete in the international tourism market, boost the quality of services and stimulate the growth of the regional economy.